Representación política en un contexto de transición. Análisis del caso de Raúl Porras Barrenechea como senador en el Congreso Peruano (1956-1958) - Casalino, Carlota (2021)
The Peruvian political transition of 1956 allowed senators like Raúl Porras Barrenechea to give more importance to the function of political representation than to other parliamentarian’s functions, such as political control, legislative issues and deliberation. The explanation for this preference lies in the need to democratize a society that during the previous government of Manuel A. Odría −the authoritarian period of eight years− had interrupted the mediation between parliament and society, and instead had generated patron-client relations between a depoliticized population and the leader in charge of the Executive Power. Hence, privileging the function of representation meant contributing to the promotion of citizenship and the channeling of demands through Parliament.